Ankylosing spondylitis of the cervical spine - a case study - Wróbel, Grzegorz; Spałek, Jakub (Journal of Education, Health and Sport, 2018)
Ankylosing spondylitis (AS), (synonyms: Bechterew’s disease, Marie Strumpell disease, rheumatoid spondylitis) is a chronic inflammatory disease that attacks the spine, causing its pain and stiffness. The severity of this disease ranges from mild to very heavy. Clinical manifestations of this disease are focused on changes in body posture, for example, inclining the body figure forward or may be a condition for severe disability. The analyzed case concerns the bone material obtained from archaeological excavations conducted in Kielce. During the osteological analysis of the female skeleton at the age of about 50 years, two vertebrae from the cervical segment were joined together. It was established that the fusion occurred between C6 and C7. In exact terms, the association occurred as a result of fusion of the vertebral body by marginal syndesmophytes and fusion of the posterior vertebral elements as well (facet joints). The exact cause of this disease is unknown. Probably for the disease to develop, several factors need to be imposed: genetic, immune (immune system disorders) and environmental factors, such as bacterial infections (especially the gastrointestinal tract and genitourinary tract).